Future Investment: The Urgency of Fulfilling the Educational Rights of Parepare Beggars and Buskers - Sri, Sri Adriana; Maslijar, Heri (JURNAL SULTAN: Riset Hukum Tata Negara, 2025)
This article aims to find out the responsibility of the Parepare City Government in fulfilling the right to education for beggars and buskers in Parepare City; and the inhibiting factors in fulfilling the right to education for beggars and buskers in Parepare City. This type of article is a field research article using a teleogic-normative, juridical, and sociological approach. The results of this article show that: 1) The role of the Education Office and the Social Service in Parepare City related to the fulfillment of the right to education for beggars and beggars in Parepare City is that the Social Service plays a role in identifying and collecting data on beggars and buskers by referring to the integrated database after the social service stage, then the social service submits data on beggars and buskers who need education to the education department, then the education office is the one who continues related to the education program for beggars and buskers through its program, namely Children Not School (ATS) 2). The fulfillment of the right to education for beggars and buskers in Parepare City is faced with various complex and interrelated obstacles. Administrative problems, such as the absence of official identity documents, and lack of information and lack of socialization about educational programs. In addition, the lack of synchronization or lack of coordination between the social service and the education service also worsens this situation, resulting in data and programs that are supposed to support each other to be ineffective and not well coordinated.